Clinical Trial Simulations From a Model‐Based Meta‐Analysis of Studies in Patients With Advanced Hepatocellular Carcinoma Receiving Antiangiogenic Therapy. (15th May 2016) - Zierhut, ML; Chen, Y; Pithavala, YK; Nickens, DJ; Valota, O; Amantea, MA
Abstract : A mixed effect model describing median overall survival (mOS) in patients with advanced hepatocellular carcinoma (aHCC) treated with antiangiogenic therapy (AAT) was developed from literature data. Data were extracted from 59 studies, representing 4, 813 patients. The final model included estimates of mOS after AAT (8.5 months) or placebo (7.1 months) administration. The mOS increased 21% when the AAT was sorafenib (SOR) or 42% when locoregional therapy was coadministered. The mOS decreased when patients received prior systemic therapy (↓7%) or concomitant chemotherapy (↓4%) or the percentage of patients with hepatitis B increased (↓∼0.4%/%). Clinical trial simulations of a phase II comparative trial predicted an mOS ratio (placebo:AAT) of 0.687 or 0.831, with a 65% or 22% probability of demonstrating superiority, for SOR or other AATs, respectively. Additionally, the 95% confidence interval (CI) of the simulated median mOS ratio for non‐SOR AATs was similar to the 95% CI of the hazard ratio (HR) observed in the trial.